Investigating the nature and properties of MAXI J1810−222 with radio and X-ray observations. Issue 4 (13th May 2022) - Russell, T D; Del Santo, M; Marino, A; Segreto, A; Motta, S E; Bahramian, A; Corbel, S; D'Aì, A; Salvo, T Di; Miller-Jones, J C A; Pinto, C; Pintore, F; et al.
ABSTRACT: We present results from radio and X-ray observations of the X-ray transient MAXI J1810−222. The nature of the accretor in this source has not been identified. In this paper, we show results from a quasi-simultaneous radio and X-ray monitoring campaign taken with the Australia Telescope Compact Array, the Neil Gehrels Swift Observatory X-ray Telescope (XRT), and the Swift Burst Alert Telescope . We also analyse the X-ray temporal behaviour using observations from the Neutron star Interior Composition Explorer. Results show a seemingly peculiar X-ray spectral evolution of MAXI J1810−222 during this outburst, where the source was initially only detected in the soft X-ray band for the early part of the outburst. Then, ∼200 d after MAXI J1810−222 was first detected the hard X-ray emission increased and the source transitioned to a long-lived (∼1.5 yr) bright, harder X-ray state. After this hard state, MAXI J1810−222 returned back to a softer state, before fading and transitioning again to a harder state and then appearing to follow a more typical outburst decay. From the X-ray spectral and timing properties, and the source's radio behaviour, we argue that the results from this study are most consistent with MAXI J1810−222 being a relatively distant (≳6 kpc) black hole X-ray binary. A sufficiently large distance to source can simply explain the seemingly odd outburst evolution that was observed, where only the brightest portion of the outburst was detectable by the all-sky XRTs .